2014
DOI: 10.1186/1471-2288-14-135
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the sample mean and standard deviation from the sample size, median, range and/or interquartile range

Abstract: BackgroundIn systematic reviews and meta-analysis, researchers often pool the results of the sample mean and standard deviation from a set of similar clinical trials. A number of the trials, however, reported the study using the median, the minimum and maximum values, and/or the first and third quartiles. Hence, in order to combine results, one may have to estimate the sample mean and standard deviation for such trials.MethodsIn this paper, we propose to improve the existing literature in several directions. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
4,991
2
15

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 7,175 publications
(5,017 citation statements)
references
References 12 publications
9
4,991
2
15
Order By: Relevance
“…Results for outcomes for which meta-analysis was deemed inappropriate because of an insufficient number of studies or clinical or statistical heterogeneity were reported in narrative form, and observational studies were reported in tabular form (Appendix 1). Where necessary to standardise reporting of central tendency between studies, we converted standard error to standard deviation, and estimated mean and standard deviation from reported median and interquartile ranges using a standard approach [11]. For key outcomes, we assessed the quality of evidence using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach [12].…”
Section: Resultsmentioning
confidence: 99%
“…Results for outcomes for which meta-analysis was deemed inappropriate because of an insufficient number of studies or clinical or statistical heterogeneity were reported in narrative form, and observational studies were reported in tabular form (Appendix 1). Where necessary to standardise reporting of central tendency between studies, we converted standard error to standard deviation, and estimated mean and standard deviation from reported median and interquartile ranges using a standard approach [11]. For key outcomes, we assessed the quality of evidence using the Grades of Recommendation, Assessment, Development and Evaluation (GRADE) approach [12].…”
Section: Resultsmentioning
confidence: 99%
“…48 Attempts have been made to improve the estimations, but they remain to be validated. 49 Therefore the methods were used as described. Survival ranges needed to estimate mean survival times were deducted from KaplanMeier curves in 6 out of 7 studies of patients with para-aortic LNM.…”
Section: Discussionmentioning
confidence: 99%
“…Standard deviations were calculated from the standard error or confidence interval (CI) if not reported. Mean baseline LDL‐C was estimated from median and interquartile range if not reported 15. Heterogeneity and inconsistency were assessed by using the Cochran Q test and I 2 statistic.…”
Section: Methodsmentioning
confidence: 99%